Safeguards Assessments : 2014 Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2014)
The safeguards policy aims to mitigate the potential risks of misuse of resources, including Fund resources, and misreporting of program monetary data. The policy, introduced in 2000, is an integral part of the Fund's financing policies and complements other safeguards, such as program design, conditionality, and access limits. Safeguards assessments of central banks of the borrowing member are required for almost all forms of Fund financing, and are followed by a period of monitoring for as long as Fund credit is outstanding.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Antigua and Barbuda